EGCG, a Green Tea Compound, Increases NO Production and Has Antioxidant Action in a Static and Shear Stress In Vitro Model of Preeclampsia - Mariana Bertozzi-Matheus; Thaina Omia Bueno-Pereira; Priscila Rezeck Nunes; Valeria Cristina Sandrim (MDPI AG, 2024)
Preeclampsia (PE) is a gestational hypertensive disease characterized by endothelial dysfunction. Epigallocatechin-3-gallate (EGCG), the main compound in green tea, is a promising therapeutic target for the disease. By activating eNOS, EGCG increased NO production and exerted an important antioxidant action, but its specific impact in the context of PE remains understudied. The aim of this study is to evaluate the effects of EGCG on endothelial function in static and shear stress in in vitro models of PE. Endothelial cells were incubated with healthy (HP) and preeclamptic (PE) pregnant women's plasma, and the latter group was treated with EGCG. Additionally, NOS (L-NAME) and PI3K protein (LY249002) inhibitors were also used. The levels of NO, ROS, and O2•− were evaluated, as well as the antioxidant potential. These investigations were also carried out in a shear stress model. We found that EGCG increases the NO levels, which were reduced in the PE group. This effect was attenuated with the use of L-NAME and LY249002. Furthermore, EGCG increased the antioxidant capacity of PE, but its action decreased with LY294002. In cells subjected to shear stress, EGCG increased nitrite levels in the PE group and maintained its action on the antioxidant capacity. This is the first study of the effects of EGCG in this experimental model, as well as the investigation of its effects along with shear stress. Our findings suggest that EGCG improves parameters of endothelial dysfunction in vitro, making it a promising target in the search for treatments for the disease.